Maharashtra State BoardHSC Arts 12th Board Exam
Advertisement Remove all ads

Inverse of the statement pattern (p ∨ q) → (p ∧ q) is - Mathematics and Statistics

Inverse of the statement pattern (p ∨ q) → (p ∧ q) is 

(A) (p ∧ q) → (p ∨ q)

(B) ∼ (p ∨ q) → (p ∧ q)

(C) (∼ p ∨ ∼ q) → (∼ p ∧ ∼ q)

(D) (∼ p ∧ ∼ q) → (∼ p ∨ ∼ q)

Advertisement Remove all ads

Solution

(D) (∼ p ∧ ∼ q) → (∼ p ∨ ∼ q)

statement pattern: (p ∨ q ) → ( p ∧ q)
Its inverse is
~ (p ∨ q ) → ~ ( p ∧ q)
≡ (∼ p ∧ ∼ q) → (∼ p ∨ ∼ q)

Concept: Mathematical Logic - Sentences and Statement in Logic
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×